2015
DOI: 10.1111/bij.12564
|View full text |Cite
|
Sign up to set email alerts
|

A chloroplast variation map generated using whole genome re-sequencing of Korean landrace rice reveals phylogenetic relationships amongOryza sativasubspecies

Abstract: Although the overall structure of the chloroplast genome is generally conserved, several sequence variations have been identified that are valuable for plant population and evolutionary studies. Here, we constructed a chloroplast variation map of 30 landrace rice strains of Korean origin, using the Oryza rufipogon chloroplast genome (GenBank: ) as a reference. Differential distribution of single‐nucleotide polymorphisms and INDELs across the rice chloroplast genome is suggestive of a region‐specific variation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…japonica is closed to Oryza rufipogon in Asian cultivated and wild rice (Brozynska et al 2014 ) and the African rice ( Oryza glaberrima and Oryza barthii ) were cluster together but in separate group with the Asian rice (Wambugu et al 2015 ). Our previous studies indicated that the use of chloroplast genome variation to study diversity, population genetics, and phylogenetic analysis was quite convincing and also supported some previous outcomes (Tong et al 2015 ). Despite these chloroplast-related studies, a large number of accessions must be applied to extend these studies from limited collections and specific varieties.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…japonica is closed to Oryza rufipogon in Asian cultivated and wild rice (Brozynska et al 2014 ) and the African rice ( Oryza glaberrima and Oryza barthii ) were cluster together but in separate group with the Asian rice (Wambugu et al 2015 ). Our previous studies indicated that the use of chloroplast genome variation to study diversity, population genetics, and phylogenetic analysis was quite convincing and also supported some previous outcomes (Tong et al 2015 ). Despite these chloroplast-related studies, a large number of accessions must be applied to extend these studies from limited collections and specific varieties.…”
Section: Introductionsupporting
confidence: 87%
“…indica and japonica , which were thought to be originated from O. nivara and O. rufipogon , respectively. According to a chloroplast whole genome sequence investigation from several references, we previously found that the indica and japonica were closer with O. nivara and O. rufipogon , respectively, which also indicated the independent origin of Asian cultivated rice (Tong et al 2015 ). Population structure of a KRICE_CORE set, which hold 137 accessions in current collection, also supported the hypothesis of the independent origin of indica and japonica in nuclear genome (Kim et al 2016 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, both inadequate informative sites of DNA sequences and a limited number of taxon sampling have sometimes led to poor phylogenetic resolution and inappropriate taxonomic treatment. The whole chloroplast genome, containing more informative sites, has been regarded as a powerful data source for resolving the phylogenetic relationships of different taxonomic ranks, especially taxa with notorious difficulty in species delimitation (Knox & Palmer, 1999;Goremykin et al, 2004;Shaw et al, 2007;Tong et al, 2015;Wen et al, 2018;Liu et al, 2019). With the development of next-generation sequencing technologies as well as the decreasing cost, it has become practical to resolve difficult phylogenies using the whole chloroplast genome (Wilkinson et al, 2017;Valcárcel & Wen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This suggest that the maternal genomes of aus come from two different origins. (Kumagai et al, 2016) (Civáň et al, 2015;Kim et al, 2015;Tong et al, 2015;Tong et al, 2016) Despite the existence of distinct clades based upon chloroplast sequence the accessions did not show a strong geographic isolation being spread widely across the south and east of Asia. Divergence may have been caused by a past period of geographic isolation creating distinct populations that became the progenitors for domestication of indica and japonica rice.…”
Section: Discussionmentioning
confidence: 88%
“…However, accessions in the O. sativa japonica sub clade extended further west into India, while the O. sativa subsp. indica were more abundant further to the south and east (Civáň et al, 2015;Garris et al, 2005;Kim et al, 2014b;Tong et al, 2015;Tong et al, 2016).…”
mentioning
confidence: 98%